If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6v=3(6v+4)
We move all terms to the left:
6v-(3(6v+4))=0
We calculate terms in parentheses: -(3(6v+4)), so:We get rid of parentheses
3(6v+4)
We multiply parentheses
18v+12
Back to the equation:
-(18v+12)
6v-18v-12=0
We add all the numbers together, and all the variables
-12v-12=0
We move all terms containing v to the left, all other terms to the right
-12v=12
v=12/-12
v=-1
| 2x+6+5x-9=60 | | 60=5x-9 | | 60=2x+6 | | x-15x+27=0 | | 72=3(x+9) | | 5.1=8-x | | 9x+5=10x+21 | | 50+x+66=70 | | -5x=5x+8 | | 7k-10k=2(3-k) | | 30+4y=-30 | | -9(n+4)=-5n+(4n+36) | | -2(x-3)=3x+46 | | 3-4a-3a=3 | | 3=3-4a-3a | | 54-30x+4x^2=0 | | -7w=14/15 | | -11=1+3k | | 12w+2w=14w | | z=8-10/2 | | 8x-5+x+5+90=180 | | 8(2a+5)=12a-(2a+14) | | 5x+30+90=25 | | 4+-2y+3=-9 | | 10=0.018268×v^2 | | 6t+7t-t+5t=2t-2t+4+9 | | 6x+8+10+6x=90 | | 5(5+2x)-3=5x(6+8) | | 5(5+2x)-3=5x+7 | | 5(5+2x)-3=5x-7 | | 5(7-2x)-3=5(3x-5) | | 5(2w+4)=35 |